The Relationship between Energy Intake, Macronutrient Intake, Nutritional Status, and Work Fatique among Shift Security Officers at State University of Surabaya - Lusia Estu Ariningtyas; Lini Anisfatus Sholihah (Ikatan Sarjana Gizi Indonesia (ISAGI), 2026)
Work fatigue is a critical issue that can reduce productivity, increase the risk of occupational accidents, and negatively affect workers’ health, particularly among shift workers. Work fatigue is influenced by various factors, including inadequate nutritional status and nutrient intake. Security personnel are a vulnerable occupational group due to high alertness demands and circadian rhythm disruption caused by shift work systems. This quantitative study employed a cross-sectional design and involved the total population of security personnel working morning, afternoon, and night shifts (24 respondents per shift) at State University of Surabaya. Data collection instrument using the Industrial Fatigue Research Committee questionnaire, 2×24-hour food recall, microtoice, and a digital scale. The results showed significant associations between carbohydrate intake (p = 0.004; r = 0.334) and protein intake (p = 0.003; r = 0.346) with work fatigue levels, while energy intake, fat intake and nutritional status was not significantly associated with work fatigue among shift security personnel at State University of Surabaya. The findings of persistently deficient dietary intake, overweight nutritional status, and high levels of work fatigue particularly among night shift workers highlights the need for regular health monitoring of workers by the outsourcing company.